Paracetamol preceding very preterm birth: Is it safe?. (15th June 2022) - Laitala, Aliisa; Saarela, Timo; Vääräsmäki, Marja; Hallman, Mikko; Aikio, Outi
Abstract: Introduction: The use of paracetamol for pain relief in pregnancy is common. However, the influence of paracetamol on the perinatal adaptation of high‐risk infants has not been studied. These data are important for safety, since another inhibitor of prostaglandin synthesis is harmful to infants born very preterm and increases serious morbidity. We studied whether the use of paracetamol had an adverse influence on neonatal adaptation and the outcomes of infants during the first hospitalization. Material and Methods: We studied the patient records of high‐risk mothers and their infants born before 32 weeks of gestation for multiple variables over a period of 84 months in Oulu University Hospital, a regional tertiary care hospital caring for high‐risk deliveries and providing neonatal intensive care. In a matched cohort setting, the exposition was defined as paracetamol use <24 h before childbirth. The controls had consumed no paracetamol up to 1 week before delivery. Infants with major anomalies were excluded. The primary outcome was defined as the need for early interventional treatments for the preterm infants. Outcomes during the first hospitalization were also studied. Results: Altogether, 170 fetuses from 149 mothers were exposed to paracetamol during the study period. The control population, delivering during the same period, consisted of 118 non‐exposed fetuses from 104 mothers. Among them, the mothers were pairwise matched according to their medications, amniotic fluid leakage time, clinical infections, and delivery mode. After matching, 72 mothers/group remained, resulting in 88 paracetamol‐exposed infants and 85 controls. No perinatal adverse reactions were detected. There were no differences in either circulatory support during the first postnatal day or in the risk for major diseases during the first hospitalization. Paracetamol‐exposed infants needed fewer acute delivery room therapies (51.1% vs 65.9%, mean difference −14.89; 95% confidence interval −0.29 to −0.003). Maternal total paracetamol dose in the 1 week before delivery correlated positively with Apgar scores. Conclusions: Antenatal paracetamol given within 24 h before birth had no adverse effects on extremely or very preterm infants. The long‐term safety of paracetamol and the potential acute benefits for preterm infants during perinatal transition remain to be proven in larger, prospective settings.